Genomic and Transcriptomic Analysis Provide Insights Into Root Rot Resistance in Panax notoginseng - Ning, Kang; Li, Mengzhi; Wei, Guangfei; Zhou, Yuxin; Zhang, Guozhuang; Huai, Hao; Wei, Fugang; Chen, Zhongjian; Wang, Yong; Dong, Linlin; Chen, Shilin (Frontiers in Plant Science, 2021)
Panax notoginseng (Panax notoginseng (Burk.) F.H. Chen), a plant of high medicinal value, is severely affected by root rot during cultivation. Here, we generated a reference genome of P. notoginseng, with a contig N50 size of 241.268 kb, and identified 66 disease-resistance genes (R-genes) as candidate genes for breeding disease-resistant varieties. We then investigated the molecular mechanism underlying the responses of resistant and susceptible P. notoginseng genotypes to F. oxysporum infection at six time points by RNA-seq. Functional analysis of the genes differentially expressed between the two genotypes indicated that genes involved in the defense response biological process like hormone transduction and plant-pathogen interaction are continuously and highly expressed in resistant genotype during infection. Moreover, salicylic acid and jasmonic acid levels gradually increased during infection in the resistant genotype. Coexpression analysis showed that PnWRKY22 acts as a hub gene in the defense response of the resistant genotype. Finally, transiently overexpressing PnWRKY22 increased salicylic acid levels in P. notoginseng leaves. Our findings provide a theoretical basis for studying root rot resistance in P. notoginseng.